2015
DOI: 10.1037/ccp0000040
|View full text |Cite
|
Sign up to set email alerts
|

Changes in posttraumatic cognitions predict changes in posttraumatic stress disorder symptoms during cognitive processing therapy.

Abstract: Findings support the hypothesized underlying mechanisms of CPT in showing that change in trauma-related cognitions precedes change in PTSD symptoms. Results suggest that reduction of depression may be important in influencing reduction of PTSD among veterans in residential PTSD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
96
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 24 publications
9
96
0
4
Order By: Relevance
“…This is consistent with the view of belief change as a process which underlies successful recovery from PTSD, regardless of whether this is achieved via PE, another treatment, or naturalistic improvement (Foa et al, 2006). Consistent with this theory, belief change has been found to precede PTSD improvement in other empirically-supported psychotherapies, including other CBTs like Cognitive Processing Therapy (Kleim et al, 2013; Schumm et al, 2015) and non-CBT approaches that are not clinically or theoretically focused on modifying trauma-related cognitions (e.g., McLean, Yeh et al, 2015; McLean, Su et al, 2015). …”
mentioning
confidence: 79%
“…This is consistent with the view of belief change as a process which underlies successful recovery from PTSD, regardless of whether this is achieved via PE, another treatment, or naturalistic improvement (Foa et al, 2006). Consistent with this theory, belief change has been found to precede PTSD improvement in other empirically-supported psychotherapies, including other CBTs like Cognitive Processing Therapy (Kleim et al, 2013; Schumm et al, 2015) and non-CBT approaches that are not clinically or theoretically focused on modifying trauma-related cognitions (e.g., McLean, Yeh et al, 2015; McLean, Su et al, 2015). …”
mentioning
confidence: 79%
“…Although it has been shown that having experienced traumatic loss is associated with an increased risk of developing PTSD (Amick‐McMullan et al., ; Boelen et al., ; Green et al., ) and higher levels of PTSD severity compared with having experienced life threat events (Litz et al., ), there are no known previous studies examining the relation between traumatic loss and PTSD treatment response compared with other types of trauma. However, this alternative model is generally inconsistent with the larger literature on the association between depression and PTSD recovery, which suggests that symptoms and diagnosis of depression predict less natural (King et al, ; Tural, Önder, & Aker, ) and treatment‐led PTSD recovery (Haagen et al., ) and that improvements in depression predict reduction in PTSD symptoms throughout PTSD treatment (Keller et al., ; Schumm et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in PTSD symptoms over the course of cognitive processing therapy (CPT) was also correlated with a reduction in symptoms of depression (Galovski et al., ; Liverant, Suvak, Pineles, & Resick, ), and sudden improvements in depression during treatment were related to better PTSD treatment response (Keller, Feeny, & Zoellner, ). To our knowledge, only one treatment study has examined the relation between depression and PTSD recovery in a veteran sample; the authors found that a reduction in symptoms of depression preceded a reduction in symptoms of PTSD in veterans engaged in CPT in a residential setting (Schumm, Dickstein, Walter, Owens, & Chard, ).…”
mentioning
confidence: 99%
“…It is theorized that sleep disruption hinders various aspects of cognitive functioning, including emotional memory consolidation and learning (Diekelmann, Wilhelm, & Born, 2009;Walker 2010). These functions are believed integral to CPT and other trauma-focused psychotherapies, which achieve symptom reduction through processing trauma-related emotions and modifying associated beliefs (Harvey et al, 2014;Resick & Schnicke, 1993;Schumm, Dickstein, Walter, Owens, & Chard, 2015;Zalta et al, 2014).…”
mentioning
confidence: 99%